Consumption Epiphany: from Abstract to Material - Lazzer, Gian Paolo (Italian Sociological Review, 2016)
This paper aims to offer a reflection on the latest developments concerning the study of consumption in the field of sociology in order to outline a conceptual, albeit not comprehensive, map. Specifically, the intention of this paper is to map a precise point of departure for the approaches which are currently better able to interpret the processes of consumption that characterise modern societies. The literature review has clearly shown a convergence of interests on consumption practices that focuses on material and tangible issues. Approaches that refer to the theories of practice, material culture and studies on science and technology (STS) inspired by the actor network theory (ANT) share an interest in this aspect by offering viewpoints which, although specific, are definitely complementary. The sociology of consumption, through an approach that is both multifaceted and focused, has a major opportunity to provide interpretative frameworks which are increasingly articulate and precise when compared to modern consumption, starting from its most tangible aspects and integrating them with the already-established symbolic aspects.